2021
DOI: 10.18332/ejm/137366
|View full text |Cite
|
Sign up to set email alerts
|

The effect of familiarization with preoperative care on anxiety and vital signs in the patient’s cesarean section: A randomized controlled trial

Abstract: INTRODUCTION Cesarean section (C-section) is one of the most prevalent surgeries among women. The preoperative stages in the surgery day and lack of control over being in an unfamiliar situation and feeling danger cause anxiety, and consequently, instability in patients. This study aimed to determine the effect of familiarization with preoperative nursing care on anxiety and vital signs of patients in cesarean section. METHODS This randomized controlled trial study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Only body temperature was not significantly different before or after the educational sessions. These findings are supported by studies conducted by [13] and [28]. In addition, Ref.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Only body temperature was not significantly different before or after the educational sessions. These findings are supported by studies conducted by [13] and [28]. In addition, Ref.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, the results showed that the mean differences in the STAI scores in terms of high overall anxiety between the intervention and control groups were significant, implying that the educational sessions effectively decreased anxiety levels among the pregnant women. Many studies have reported that pregnant women who attend appropriate educational sessions before their deliveries have lower anxiety levels compared to other pregnant women who receive no educational sessions [12,27,28]. In our study, we used the booklet not only for instructional purposes but also for reinforcement and future reference.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for the differences between our results and the published report may include different previous experiences with a CS including the indication of a previous CS, variations in preoperative care in different countries, complications during the procedure or anaesthesia, and familiarity with the settings of a CS. Mostafayi et al [ 22 ] showed that familiarity with preoperative care about a CS is associated with lesser anxiety scores and different indications for the CS. In our cohort, while women who had a CS performed for foetal indication reported higher anxiety scores, the association was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%